MOTIVASI MAHASISWA IAIN BUKITTINGGI YANG BERLATAR BELAKANG SMA DALAM MEMILIH PRODI PAI - Ade Ilham SY; Alimir Alimir (KOLONI, 2022)
This research was motivated by the problems found at IAIN Bukitinggi, among others, not graduating at another PTN, not on their own volition (parental encouragement), and joining friends. Therefore, researchers are interested in examining what is the motivation of IAIN Bukittinggi students with high school backgrounds in choosing PAI study programs. This type of research is a field research that is descriptive qualitative in nature, which tries to describe, describe and interpret a phenomenon that occurs according to the data in the field. With key informants, namely students and fathers, lecturers as supporting informants. To collect data the author uses the methods of observation, interviews, and documentation as a data collection tool, and data analysis techniques using data reduction, data display and data verification, and the validity of the data by comparing the results of observations with interviews. Based on the results of research interviews with several sources, the authors conclude the research as follows. the motivation of other Bukittinggi students with high school backgrounds in choosing the PAI study program. As for the reasons for the motivation of other students from Bukittinggi with high school backgrounds in choosing the PAI study program, it was their own will that made them motivated to continue their education at the IAIN Bukittinggi university by taking the PAI study program, they realized that the religious knowledge they had was very minimal and many of them who want to acquire religious knowledge with the aim of becoming a teacher and useful for the family, community, nation and state, there is encouragement from parents who want their children to study religion because their parents feel that the religious knowledge given to their children is not enough and their parents want his son.  Keyword: Motivation, Students of IAIN Bukittinggi, PAI